The assessment of psychological strain in work contexts - Concerning the structural equivalency of nine language adaptations of the irritation scale - Mohr, Gisela; Mueller, Andreas; Rigotti, Thomas; Aycan, Zeynep; Tschan, Franziska (My University, 2006)
Irritation as defined in this paper is the subjectively perceived emotional and cognitive strain in occupational contexts. The structural equivalence of the Arabic, Dutch, English, French, Italian, Russian, Spanish, Turkish, and Polish adaptations of the German Irritation Scale is examined. The Irritation Scale is recommended for application particularly in occupational contexts. In this field it can be used for evaluating interventions, for research on stress at work, and for individual counseling. Exploratory factor analyses, as well as single group and different multiple-group confirmatory factor analyses, were performed, Structural equivalency in terms of equal factor loadings as well as equal factor covariances across all adaptations can be claimed. However, the single group analyses suggest that the hypothesized factor model should be rejected in the English, Russian, Spanish, and Turkish versions, mainly because of borderline values in the RMSEA index.
Keywords: irritation; cognitive; emotional; measure; strain; MEASUREMENT INVARIANCE; FIT INDEXES; DYSPHORIC RUMINATION; DEPRESSED; MOOD; MENTAL STRAIN; SYMPTOMS